Photosensitizing properties of dissolved organic carbon in Canadian prairie pothole wetland ponds change in response to sunlight. Issue 4 (2nd October 2022) - Tran, Linh N.; Vu, Hoang; Hall, Britt D.
Abstract: Dissolved organic carbon (DOC) is an important component of the global carbon cycle providing ecological services such as carbon sources for microorganisms and the provision of a protective barrier between ultraviolet radiation and aquatic organisms. Our study examined the impacts of photodegradation on the optical properties of DOC in prairie wetland ponds in central Saskatchewan, Canada. Surface water was collected from two ponds with seasonal average DOC concentrations of 71.1 mg L −1 (More-DOC Pond) and 32.7 mg L −1 (Less-DOC Pond) and filtered through 1.2 µm GF/Fs into Teflon bottles transparent to UV light. Samples divided into dark and light treatments were incubated in situ at three different depths (surface, 0.25m, and 0.5 m) and collected every 2 weeks for 4 months. Excitation emission matrix scans from 300 to 800 nm and absorbance at 254 nm were measured. Absorbance at 254 nm in the More-DOC Pond and Less-DOC Pond waters decreased by 34% and 50%, respectively. Two fluorescence components were identified corresponding to previous published peaks C and M. Although bulk DOC concentrations did not show significant differences over time, fluorescence intensity of peak C decreased by 39% and 47%, and of peak M increased by 19% and 29%, in the More-DOC Pond and Less-DOC Pond, respectively. Increases in other fluorescence indicators such as fluorescence index (35% and 22%) and FRESH (29% and 30%) were also observed. Overall, terrestrial DOC from our sampling ponds became less aromatic, more aliphatic, of lower molecular weight, and lost absorptivity and fluorescence intensity after 12 weeks of incubation. Results of this study will provide a better understanding of optical characterizations and sources of DOC, and act as a foundation to further study on the role of DOC in prairie wetland ponds.